Reviewing the bibliometrics of metal-organic frameworks for hydrogen storage - Siti Nurqurratulainie, Miskan; Bashir, Abubakar Abdulkadir; Herma Dina, Setiabudi (John Wiley and Sons Inc., 2025)
Bibliometric analysis is the quantitative examination of bibliographic data. It offers a predominant overview of a study domain that can categorize articles, authors, and publications. This report provides a bibliometric analysis of research on metal-organic frameworks (MOFs) for solid-state hydrogen storage applications. The primary aim of this study is to identify significant research and emerging trends in this subject based on data from the Scopus database. MOFs are highly porous crystals with remarkable adsorption capabilities and are regarded as premier additions for improving solid-state hydrogen storage. MOFs serve as efficient adsorbents owing to their exceptional capacity to absorb gases at low temperatures and elevated pressures via physisorption. A total of 1365 journal publications were obtained from Scopus through a bibliometric review approach. The search criteria were employed to identify publications released between 2003 and 2024. The search began on March 19, 2024. Initially, the study examined the attributes of publications and citations utilizing established bibliometric markers. Secondly, the prominent countries/regions and significant institutions involved in publications concerning MOFs for hydrogen storage were present. Subsequently, this study demonstrates science mapping analysis utilizing the visualization application, VOS Viewer. Co-occurrence analysis of keywords is employed to identify the journal's prevailing subjects and trends. Ultimately, the study examines the journal's prospects based on the aforementioned study. The findings provide valuable insights for researchers to understand the extent of MOF research in hydrogen storage, facilitating the exploration of significant studies and the formulation of topics for future investigations.